Análisis y simulación del uso de ondas radioeléctricas para la detección de la concentración de los principales nutrientes en el suelo - Fonseca Carrión, Gabriela Alexandra (2016)
The purpose of this paper is show an alternative to traditional analysis of soil nutrients through the use of electromagnetic waves. A subsurface radar is proposed to detect the concentration of major nutrients (nitrogen, phosphorus and potassium) to the depth where they are into the soil, through the principles of the incident and reflected waves, in agricultural clay soil. These situations were simulated in Matlab by solving the one-dimensional discrete equations of Ampere and Faraday Through the mathematical algorithm in the Finite Difference Time Domain (FDTD). The simulation showed the direct relationship between amplitude of the reflected wave and concentration in each nutrient.